2009
DOI: 10.1183/09031936.00049008
|View full text |Cite
|
Sign up to set email alerts
|

Screening for pulmonary arteriovenous malformations using transthoracic contrast echocardiography: a prospective study

Abstract: Pulmonary arteriovenous malformations (PAVMs) are associated with severe neurological complications in patients with hereditary haemorrhagic telangiectasia (HHT). The objective of the present study was to prospectively establish the diagnostic value of transthoracic contrast echocardiography (TTCE) as a screening technique for PAVM using chest highresolution computed tomography (HRCT) as the gold standard for PAVMs.All consecutive adult patients referred for HHT screening underwent a chest HRCT (n5299), TTCE (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 38 publications
1
50
0
Order By: Relevance
“…Pulmonary and cerebral AVMs can cause complications, such as intracranial bleeding, brain abscess, ischaemic stroke and pulmonary haemorrhage, and screening of at-risk populations has been advocated [23][24][25][26][27][28][29][30][31][32]. Studies in adult patients have demonstrated that significant pulmonary and cerebral AVMs can be detected in asymptomatic patients [5,6,22,[31][32][33][34][35][36][37][38][39], and that preventative treatment can reduce the rate of complications [32]. This is less well established in children, and recent studies have suggested that the overall rate of complications is low in this age group [23,32].…”
mentioning
confidence: 99%
“…Pulmonary and cerebral AVMs can cause complications, such as intracranial bleeding, brain abscess, ischaemic stroke and pulmonary haemorrhage, and screening of at-risk populations has been advocated [23][24][25][26][27][28][29][30][31][32]. Studies in adult patients have demonstrated that significant pulmonary and cerebral AVMs can be detected in asymptomatic patients [5,6,22,[31][32][33][34][35][36][37][38][39], and that preventative treatment can reduce the rate of complications [32]. This is less well established in children, and recent studies have suggested that the overall rate of complications is low in this age group [23,32].…”
mentioning
confidence: 99%
“…Recent literature [9] has highlighted the possibility that TTCE alone may be sufficient for screening purposes, although this remains controversial.…”
Section: Resultsmentioning
confidence: 99%
“…TTCE alone [8] or in combination with plain chest radiography [5] has been reported to be 100% sensitive for, and able to definitively rule out, PAVMs in patients with shunts. At least some authors have argued, however, that addition of plain chest radiography to TTCE exposes patients to ionizing radiation without demonstrated improvement in detection of PAVMs [9] . Given the need for lifelong screening required in HHT, minimizing use of modalities which utilize ionizing radiation is preferred to reduce the cumulative lifetime radiation exposure [1,5] .…”
Section: Discussionmentioning
confidence: 99%
“…With a prevalence of 30 to 40%, it is difficult to argue the existence of a PFO if intravenously injected saline contrast bubbles appear in the left heart. Alternatively, saline contrast echocardiography as a technique for intrapulmonary right-to-left shunts remains less well established, despite the fact that it is more sensitive than pulmonary angiography for detection of even the smallest right-to-left intrapulmonary shunts (Cottin et al, 2004;van Gent et al, 2009).…”
Section: Theorymentioning
confidence: 99%
“…The second injection should confirm the presence of an intracardiac shunt if there is increased contrast and/or if the contrast bubbles continue to appear in the left heart in ≤ 3 heartbeats. Alternatively, if saline contrast bubbles appear in the left heart in > 3 heartbeats after their appearance in the right heart, then an intrapulmonary shunt is suspected, e.g., pulmonary arteriovenous malformation, pulmonary arteriovenous anastomoses (Nanthakumar et al, 2001;Lee et al, 2003;van Gent et al, 2009;Elliott et al, 2011a). The different types of intracardiac and intrapulmonary shunts are outlined in detail below.…”
Section: Differentiating Between Intrapulmonary and Intracardiac Shuntmentioning
confidence: 99%